Exploring the Representation and Implementation of Sustainable Development in Finnish Universities' Strategies - Pasynkov, Maksim (My University, 2024)
This study investigates how Finnish universities represent and conceptualize sustainable development in their strategic documents. The research focuses on eight classical research universities in Finland, analyzing their most recent strategy documents using an approach inspired by Carol Bacchi's "What's the Problem Represented to be?" (WPR) method. The theoretical framework of the study integrates perspectives on sustainable development in higher education, strategic management, and policy analysis. It explores various interpretations of sustainable development, including the three pillars approach (economic, ecological, and social), the UN Sustainable Development Goals (SDGs) framework, ecological emphasis, and social emphasis. The findings reveal a strong commitment to sustainable development across the Finnish higher education sector, with sustainability integrated into core university activities including research, education, and societal impact. Common themes emerge across the strategies, such as interdisciplinary approaches, alignment with SDGs, open science, and balancing global challenges with regional development. However, the analysis also uncovers significant differences in how universities approach sustainability. Each institution emphasizes unique areas that align with their specific strengths and regional contexts. The study contributes to the theoretical understanding of sustainability in higher education by highlighting the need for more nuanced and flexible models that can accommodate the complex, multi-faceted approaches observed. It also demonstrates the value of applying critical policy analysis approaches like WPR to university strategic documents. Practical implications for university leaders and policymakers include the importance of holistic integration of sustainability across all university activities, leveraging institutional strengths and regional contexts, and fostering interdisciplinary collaboration and stakeholder engagement. The research has some limitations, including its focus on strategic documents alone and the specific Finnish context. Future research directions could include longitudinal studies, comparative analyses across different national contexts, and investigations into the practical implementation and impact of these sustainability strategies.
Keywords: sustainable development, higher education, strategic management